2021
DOI: 10.1007/s11557-021-01720-w
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and molecular survey of Neoconidiobolus reveals a new species and two new combinations

Abstract: The genus Neoconidiobolus was recently established to accommodate all members of the Conidiobolus subgenus Conidiobolus. Based on mitochondrial small subunit (mtSSU), nuclear large subunit (nucLSU) of rDNA and translation elongation factor 1-alpha (TEF1), this study further resolved the genus Neoconidiobolus into three clades, with three new taxa being added. They are N. kunyushanensis B. Huang & Y. Nie, sp. nov., N. lamprauges (Drechsler) B. Huang & Y. Nie, comb. nov., and N. nanodes (Drechsler) B. Huang & Y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The gene sequences annotated as “elongation factor 1α” were used in some recent taxonomic and phylogenetic studies of Conidiobolus s.l. (Nie et al 2020; Cai et al 2021; Nie et al 2021). Our gene tree analysis showed that these elongation factor genes from Conidiobolus s.l.…”
Section: Discussionmentioning
confidence: 99%
“…The gene sequences annotated as “elongation factor 1α” were used in some recent taxonomic and phylogenetic studies of Conidiobolus s.l. (Nie et al 2020; Cai et al 2021; Nie et al 2021). Our gene tree analysis showed that these elongation factor genes from Conidiobolus s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are still many other taxonomic challenges to be resolved in the future, such as replacing the missing ex-type Co. utriculosis and assigning Co. coronatus as the epitype of Conidiobolus s.s., isolating lost ex-types to confirm their taxonomic placements etc. ( Nie et al 2018 , 2020 , 2021 ; Cai et al 2021 ). For the first time, this study used partial sequence data from nucLSU , mtSSU and EFL genes to identify two new species of Capillidium from China, increasing the total number of species in the genus to ten.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, most published Conidiobolus species had been described by only one strain, with the exception of some pandemic species (e.g., C. coronatus, N. osmodes, and N. thromboides) (Nie et al 2021). Unfortunately, the type species C. utriculosus Brefeld, along with other important ex-types are missing, which makes it difficult to determine the exact taxonomic placement of some questionable Conidiobolus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic analyses have shown that is it not only Conidiobolus parvus that has questionable taxonomic placement. Our recent research has indicated that C. lampragues and C. nanodes should be assigned into the genus Neoconidiobolus (Nie et al 2021). In this article, we describe a new genus, Azygosporus gen. nov., and a new species, A. macropapillatus sp.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation